Identificação e quantificação de fungos e aflatoxinas em amendoim (Arachis hypogaea L) - MARTINS, Rosália de Fátima Ferreira (2023)
Peanut (Arachis hypogaea L) is one of the most consumed foods in the world due to its high nutritional value and availability. However, it is one of the grains most susceptible to contamination by fungi and toxins, causing great public health concern. The present study aimed to identify and quantify fungi and aflatoxins in peanuts. To this end, analyzes of the moisture content of the grains were carried out; mold quantification; identification of fungal species, by proteomic analysis, MALDI-TOF System, in addition to identifying and quantifying levels of aflatoxins in peanuts. 24 samples were analyzed, divided into 3 categories, 14 fresh samples, 05 Industrialized, and 05 Toasted. The values found for humidity ranged from 3.1% to 8.1%, suitable for controlling fungal contaminants. For the mold count of the 24 samples analyzed, only 15 (62.5%) samples were considered satisfactory, while 09 (37.5%) samples were unsatisfactory. Fungal analyzes revealed the highest incidence for the genus Aspergillus 41 (95.3%) samples, and regarding the species, A. flavus wasthe most evident 17 (39.5%)samples, followed by A. montevidensis 10 (23, two%); A. niger 10 (23.2%); A. minisclerotigenes 03 (6.9%); A. parasiticus 01 (6.9%), Purpureolicilium lilacinum 1 (2,3%)and Rhizopus sexualis 01 (6.9%). Regarding the identification and quantificationof aflatoxins, only 09 (37.5%) samples had total aflatoxins detected, which ranged from 1 to 82.3 μg/Kg. These results proved that in relation to aflatoxins, peanuts do not represent a danger for eventual ingestion, however, other mycotoxins can be produced bythese same strains of fungi. We conclude that new monitoring studies are necessary, dueto the climatic impacts on A. flavus, due to its high capacity for environmental adaptation, as well as the greater expression of some mycotoxins and the suppression of others.